Pengembangan Buku Saku Rumus Matematika Berbasis PjBL Dalam Meningkatkan Hasil Belajar Siswa di Madrasah Ibtidaiyah - Nahdhiyah, Ni'matun (Dawuh Guru: Jurnal Pendidikan MI/SD, 2025)
Mathematic is the science of logic that studies number theory, geometry, algebra, analysis and set theory. Mathematics is often referred to as the exact. Apart from that, mathematics is also often referred to as the exact science that is most feared by most students, especially at the elementary school level. Many students are less interested in learning because the learning media used by teachers is less interesting, so teaching materials in the form of mathematical formula pocket books are needed to improve student learning outcomes. This research aims to develop a projet based learning (PjBL) based mathematical formula pocket book that can be used to improve student learning outcomes in mathematic subjects. The research method used is research and development with thw ADDIE developmet model which has five stages. Feasibility test by material experts, media experts, subject teachers and students. The data collection technique for this research is through interviews and questionnaires. The results of the feasibility test research are as follows: 1) based on material experts, an average of 3.4 was obtained with a very feasible category; 2) based on media experts, an average of 3.8 was obtained in the very appropriate category; 3) based on mathematics subject teachers, an average of 3.3 was obtained with a very decent category.